2013
DOI: 10.1021/jp409985h
|View full text |Cite
|
Sign up to set email alerts
|

Conformation and Dynamics at a Flexible Glycosidic Linkage Revealed by NMR Spectroscopy and Molecular Dynamics Simulations: Analysis of β-l-Fucp-(1→6)-α-d-Glcp-OMe in Water Solution

Abstract: The intrinsic flexibility of carbohydrates facilitates different three-dimensional structures in response to altered environments. At glycosidic (1→6)-linkages three torsion angles are variable and herein the conformation and dynamics of β-L-Fucp-(1→6)-α-D-Glcp-OMe are investigated using a combination of NMR spectroscopy and molecular dynamics (MD) simulations. The disaccharide shows evidence of conformational averaging for the ψ and ω torsion angles, best explained by a four-state conformational distribution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 69 publications
5
30
0
Order By: Relevance
“…However, the effect on the determined effective distances under conditions similar to those used in this study has recently shown to be negligible. 102 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effect on the determined effective distances under conditions similar to those used in this study has recently shown to be negligible. 102 …”
Section: Methodsmentioning
confidence: 99%
“…Good agreement was found for ω conformational sampling in comparison to NMR spectroscopy and X-ray crystallography results. 73,74 While the above studies have yielded insights into the conformational properties of several disaccharides, concerns with respect to force field accuracy, diversity in the systems, and insufficient sampling of conformational space 23,37,67,7376 warrant further studies of these biologically interesting systems. 77 …”
Section: Introductionmentioning
confidence: 99%
“…NMR experiments were carried out at 300 K on a 600 MHz Bruker AVANCE III spectrometer equipped with an inverse detection probe. The proton-proton cross-relaxation rate for the H1-H2 pair in a-cellobiose was measured using 1D 1 H, 1 H-NOESY experiments (Stott et al, 1997), and that of H4-H1 0 employed a 1D 1 H, 1 H-STEP-NOESY experiment (Hu et al, 2004;Pendrill et al, 2013). In all cases, selective excitation was achieved by single or double PFGSE modules utilizing 50-msec r-SNOB-or i-SNOB-2-shaped pulses for the NOESY experiment, and 50-65-msec r-SNOB-shaped pulses for the STEP-NOESY experiment.…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…In those cases, Karplus-relations for the two different diastereotopic protons H6 pro-R and H6 pro-S and their coupling to C4 and H5 have been developed. [25][26][27][28][29][30] However, to the best of our knowledge, there do not seem to be any publications that propose a quantitative description of dihedral angles  and  (i.e. ') for 6-O-substituted sugars based on a Karplus-relation for coupling of H6-C4.…”
mentioning
confidence: 99%